Comparison of coronary bifurcation lesions stenting techniques- a network meta-analysis. (25th November 2020) - Barrett, O; Hadad, L; Abramowitz, Y; Cafri, C; Rosenstein, G; Merkin, M; Zahger, D; Koifman, E
Abstract: Background: Coronary bifurcations lesions (CBL) are account for 15–20% of all percutaneous coronary interventions (PCI) and constitute a major challenge for interventionists in terms of procedural success rate and long-term cardiac events. Based on data from multiple randomized trials and registries, current guidelines advocate the use of provisional side branch (SB) stenting strategy for the majority of CBL's. However, for true or complex CBL's (long side branches lesions, difficult side branches access or high risk of side branches compromise), which account for up to 25% of CBL's, this strategy may by unsafe and ineffective due to a potential risk of intraprocedural or long-term occlusion of a significant side branch and a two-stenting technique may be needed in order to achieve optimal results. Up to date, the optimal two- stenting technic for CBL remains in debate. Accordingly, our aim was to compare different stenting techniques in coronary bifurcation lesions. Methods: We performed a MEDLINE search for randomized controlled trials (RCT) and observational studies comparing stenting techniques in CBL's with reported clinical outcomes. Mixed treatment comparison model generation was performed to directly and indirectly compare culotte, T and protrusion (TAP), crush and provisional techniques Results: A total of 13 RCT and 12 observational studies were identified including 6806 patients, among whom 1, 201 were treated with cullotte, 2, 731 with crush, 797 with TAP and 2077 with provisional stenting. The Bayesian hierarchical random-effects model demonstrated a significant reduction in target lesion revascularization (TLR) rate with crush techniques compared with provisional technique (OR 0.64 95% CI 0.42–0.97) along with a trend for reduction in major adverse cardiovascular (MACE) events (OR 0.75, 95% CI 0.55–1.02). TAP and culotte techniques did not show similar results. Equality of other endpoints, including mortality, myocardial infarction and re-stenosis was found between all CBL's techniques (Figure 1). Discussion: Our findings suggest improved outcomes with crush technique compared to other double stenting techniques in terms of TLR with a trend towards MACE reduction. Further research is required to determine the optimal stenting technique for coronary bifurcations lesions along with the utility of imaging and physiology in this complex subset. Funding Acknowledgement: Type of funding source: None